2008
DOI: 10.1617/s11527-008-9439-x
|View full text |Cite
|
Sign up to set email alerts
|

Formation and properties of C-S-H–PEG nano-structures

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 44 publications
(51 reference statements)
3
37
0
1
Order By: Relevance
“…An additional test was performed using higher loads (matrix 2) in order to cover a greater region and, principally, to make marks that would be visible under SEM. In this case, a 2 × 3 points matrix was used up to a load of 512 mN (1,2,4,8,16,32,64,128,256, and 512 mN). Loading was applied linearly for 10 s, the maximal load (P max ) was then maintained for 5 s and unloading occurred over a further 10 s.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional test was performed using higher loads (matrix 2) in order to cover a greater region and, principally, to make marks that would be visible under SEM. In this case, a 2 × 3 points matrix was used up to a load of 512 mN (1,2,4,8,16,32,64,128,256, and 512 mN). Loading was applied linearly for 10 s, the maximal load (P max ) was then maintained for 5 s and unloading occurred over a further 10 s.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the nanostructural interaction, the science is incipient, but it can be inferred that polymers alter the gel volume of the C-S-H formed and that these modifications make it more resistant to gas and liquid penetration, thus making it more durable [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (Sant, 2009) reported a reduction in the SRA peak with time, which was attributed to a reduction in SRA concentration in the pore solution due to SRA uptake by hydration products. This can explain the difference between the 12 and 24 h TGA results, where the peak corresponding to SRA disappeared for the P-SRA mixture at 24 h while another peak was detected at 8008C, which corresponds to the SRA taken in the CSH gel (Beaudoin et al, 2008).…”
Section: Magazine Of Concrete Researchmentioning
confidence: 91%
“…An intimate structural description of C‐S‐H is needed to model crystallization and growth of this major phase involved in cement set and hardening, but structural information alone is not sufficient. A number of almost untouched issues include the structural incorporation of the organic additives , the role of impurities and disorder in the long‐term durability of these phases, and the possible structural role of C‐S‐H in the stabilization of hazardous or toxic species.…”
Section: Open Problemsmentioning
confidence: 99%